2020
DOI: 10.1166/jbn.2020.2986
|View full text |Cite
|
Sign up to set email alerts
|

A Tenofovir-Loaded Glycyrrhetinic Acid-Modified Cationic Liposome for Targeted Therapy of Hepatitis B Virus

Abstract: Tenofovir (TFV), an acyclic nucleoside analog, exhibits potent anti-HBV activity. However, poor bioavailability, nephrotoxicity and bone toxicity limit its further clinical application. In this work, a novel tenofovir-loaded glycyrrhetinic acidmodified cationic liposome (TGCL) was prepared for targeted therapy of HBV. The TGCL had an average particle size of 107.39 ± 1.21 nm and an entrapment efficiency of 89.83 ± 2.70% with a positive zeta potential of 37.63 ± 1.22 mV. The results of in vitro indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…GL or its medicinal preparation shows strong inhibition of the replication of several viruses in vitro : Epstein‒Barr virus (EBV), herpes simplex virus (HSV), hepatitis A/B/C virus (HAV, HBV, HCV), human cytomegalovirus (CMV), human immunodeficiency virus (HIV), influenza virus (H3N2), SARS coronavirus, influenza A virus (IAV), influenza A virus (H5N1), and varicella-zoster virus (VZV) all show good sensitivity to GL in vitro ( Yao et al, 2020 ; Baltina and Kondratenko, 2021 ). The effect of GL plus vitamin C against pneumonia caused by infection with SARS-CoV-2 was tested in a clinical trial ( http://www.chictr.org.cn/ ).…”
Section: Resultsmentioning
confidence: 99%
“…GL or its medicinal preparation shows strong inhibition of the replication of several viruses in vitro : Epstein‒Barr virus (EBV), herpes simplex virus (HSV), hepatitis A/B/C virus (HAV, HBV, HCV), human cytomegalovirus (CMV), human immunodeficiency virus (HIV), influenza virus (H3N2), SARS coronavirus, influenza A virus (IAV), influenza A virus (H5N1), and varicella-zoster virus (VZV) all show good sensitivity to GL in vitro ( Yao et al, 2020 ; Baltina and Kondratenko, 2021 ). The effect of GL plus vitamin C against pneumonia caused by infection with SARS-CoV-2 was tested in a clinical trial ( http://www.chictr.org.cn/ ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, GL and GLA have antiviral and hepatoprotective effects (X. Shi, Yu, Zhang, & Liu, 2020; Sun, Zhao, Lu, & Yang, 2019), LI has anti‐inflammatory and antitussive effects (Lee, Park, Kim, & Lee, 2019), ISL has anti‐oxidative and anticancer activities, and LIQ has antimicrobial effects (Peng, Du, Peng, & Wang, 2015; Salvatore, 2016). GL can inhibit viral hemorrhagic septicemia virus (Lim et al, 2021), HIV (Ito, Sato, Hirabayashi, & Tanabe, 1988), and influenza virus H5N1 (Michaelis, Geiler, Naczk, & Sithisarn, 2011); GLA fights hepatitis B virus infection (Yao, Liu, Luo, & He, 2020); LIQ can resist methicillin‐resistant Staphylococcus aureus (Salvatore, 2016). In view of these reports, we evaluated the components of G. uralensis for their anti‐SGIV effects, but we found that none of them had antiviral activity against SGIV infection.…”
Section: Discussionmentioning
confidence: 99%